CDKN1C mutation affecting the PCNA-binding domain as a cause of familial Russell Silver syndrome. Issue 12 (24th September 2013) - Brioude, F; Oliver-Petit, I; Blaise, A; Praz, F; Rossignol, S; Jule, M Le; Thibaud, N; Faussat, A-M; Tauber, M; Bouc, Y Le; Netchine, I
Abstract : Background: Russell Silver syndrome (RSS) leads to prenatal and postnatal growth retardation. About 55% of RSS patients present a loss-of-methylation of the paternal ICR1 domain on chromosome 11p15. CDKN1C is a cell proliferation inhibitor encoded by an imprinted gene in the 11p15 ICR2 domain. CDKN1C mutations lead to Beckwith Wiedemann syndrome (BWS, overgrowth syndrome) and in IMAGe syndrome which associates growth retardation and adrenal insufficiency. We searched for CDKN1C mutations in a cohort of clinically diagnosed RSS patients with no molecular anomaly. Method: The coding sequence and intron–exon boundaries of CDKN1C were analysed in 97 RSS patients. The impact of CDKN1C variants on the cell cycle in vitro were determined by flow cytometry. Stability of CDKN1C was studied by western immunoblotting after inhibition of translation with cycloheximide. Results: We identified the novel c.836G>[G;T] (p.Arg279Leu) mutation in a familial case of intrauterine growth retardation (IUGR) with RSS phenotype and no evidence of IMAGe. All the RSS patients inherited this mutation from their mothers (consistent with monoallelic expression from the maternal allele of the gene). A mutation of this amino acid (p.Arg279Pro) has been reported in cases of IMAGe. Functional analysis showed that Arg279Leu (RSS) did not affect the cell cycle, whereas the Arg279Pro mutation (IMAGe) led to a gain of function. Arg279Leu (RSS) led to an increased stability which could explain an increased activity of CDKN1C. Conclusions: CDKN1C mutations cause dominant maternally transmitted RSS, completing the molecular mirror with BWS. CDKN1C should be investigated in cases with family history of RSS.